Inovasi dalam Proses Operasional Kantor Konsultan Pajak: Penerapan Matriks Pengendalian Transaksi sebagai Strategi Preventif Kesalahan Pelaporan - Sabrina Aulia Istiqfarah; Ajeng Tita Nawangsari (AKUNTANSI 45, 2025)
This study aims to implement the Transaction Control Matrix as an operational process innovation to prevent financial and tax reporting violations at Tax Consultant Offices (KKP). The research method used is a descriptive qualitative approach with a case study approach, through in-depth interviews and direct observation of the report preparation process. The results indicate that the control matrix functions as an effective preventive instrument through a systematic reconciliation mechanism between bank statements and transaction documents, thus enabling early detection of discrepancies such as fictitious invoices or recording errors. In addition to improving the accuracy of Periodic VAT Tax Return reporting, this matrix also has multifunctional value as an accounting management tool, increasing audit efficiency, and providing a source of analytical data for clients. Implementation of the matrix strengthens the COSO Framework-based internal control system and transforms the KKP's role from a compliance service provider to a strategic partner. This study recommends the Transaction Control Matrix as a best practice for continuously improving the quality of KKP services